2016
DOI: 10.1016/j.jgeb.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and phylogenetic characterization of Listeria monocytogenes isolated from processed meat marketed in Egypt

Abstract: Because of its high case fatality rate, listeriosis locates among the most frequent causes of death due to food-borne illness. In this study, a total of 150 processed meat samples were collected from Giza Governorate, Egypt. Phenotypic and genotypic identification of Listeria monocytogenes was performed using PCR incorporating listeriolysin O virulence gene hlyA followed by DNA sequence analysis. L. monocytogenes was confirmed in 4% of each of beef burger, minced meat, and luncheon samples. Phylogenetic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
3
3
0
Order By: Relevance
“…Although other studies reported a lower prevalence of L. monocytogenes. For example, bacteria were detected in 5.3% of meat products in China (24), 4% in Egypt (25) and 0.7% in Estonia (26). In the current study, the prevalence of L. monocytogenes in roasted fish, roasted chicken meat and cocked beef were similar to that in Shi et al study (23); in which, L. monocytogenes was recovered from 6.9% of Chinese roast chicken meats and 6.5% of Chinese cocked beef.…”
Section: Discussionsupporting
confidence: 80%
“…Although other studies reported a lower prevalence of L. monocytogenes. For example, bacteria were detected in 5.3% of meat products in China (24), 4% in Egypt (25) and 0.7% in Estonia (26). In the current study, the prevalence of L. monocytogenes in roasted fish, roasted chicken meat and cocked beef were similar to that in Shi et al study (23); in which, L. monocytogenes was recovered from 6.9% of Chinese roast chicken meats and 6.5% of Chinese cocked beef.…”
Section: Discussionsupporting
confidence: 80%
“…In this study, the diagnosis of L. monocytogenes isolates from clinical and food samples was confirmed using PCR, identified 13 L. monocytogenes isolates sheltering hly A gene, which agree with other previous studies such as [18] in Egypt who mentioned that all L. monocytogenes isolates are positive for hlyA gene from meat. Furthermore, Kamar et al [19], in Egypt, detected hlyA gene in all L. monocytogenes isolated from different sources.…”
Section: Discussionsupporting
confidence: 90%
“…The minced meat samples were totally negative in all the three companies (table 1). These results were agreed with (Mohamed et al, 2016) who found that L. monocytogenes were confirmed distributed in beef burgers samples (4%), minced meat (4%) and Luncheon (4%).…”
Section: Morphological Characterization Of Bacteria On Specific Mediusupporting
confidence: 92%